2013
DOI: 10.4103/0300-1652.119636
|View full text |Cite
|
Sign up to set email alerts
|

Diseases mortality patterns in elderly patients: A Nigerian teaching hospital experience in Irrua, Nigeria

Abstract: Background:Currently, in developing countries, there is a paradigm shift in the mortality patterns from communicable to non-communicable diseases.Objective:This study is aimed at providing a broad spectrum on the mortality patterns in elderly within a 5-year-period in a tertiary healthcare provider in Nigeria.Materials and Methods:This study is a retrospective review of mortality patterns of elderly patients from January 2007 to December 2011 occurring in Irrua specialist teaching hospital, (ISTH), Irrua and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In the outcome analysis, this study observed an in-hospital mortality rate of 24.2% while 68.9% were discharged. Our findings on mortality is much higher than 8.5%, 12%, 16.4%, and 14.9% previously reported in Turkey, Portugal, Brazil, and Italy [ 16 19 ] in a similar population but close to what was observed in Nigeria (18.7%) within a related teaching hospital [ 20 ]. Again, our findings are the first to show such a high mortality in this population and require deeper investigations in future studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the outcome analysis, this study observed an in-hospital mortality rate of 24.2% while 68.9% were discharged. Our findings on mortality is much higher than 8.5%, 12%, 16.4%, and 14.9% previously reported in Turkey, Portugal, Brazil, and Italy [ 16 19 ] in a similar population but close to what was observed in Nigeria (18.7%) within a related teaching hospital [ 20 ]. Again, our findings are the first to show such a high mortality in this population and require deeper investigations in future studies.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, the WHO predicts that by 2020, noncommunicable diseases such as heart disease, cancer, and diabetes will be among the main causes of mortality in the African region [ 21 ]. Already high incidences of cerebrovascular accident (25.1%) have been reported predominantly besides malignancies (15.2%), diabetes mellitus (8%), and congestive cardiac failure (6.2%) [ 20 ]. Others include septicemia (5.2%), trauma (4.6%), renal failure and chronic obstructive pulmonary disease (3.9%).…”
Section: Discussionmentioning
confidence: 99%
“… 4 This change will have a direct impact on the pattern of admission in the medical ED, and by extension the pattern of mortality. With the obvious paradigm shift from communicable to non-communicable diseases in developing countries 5 – 8 , the impact of epidemiological transition and the response by health care providers can be further assessed by reviewing medical mortality in health care facilities, especially the ED 2 , 6 . Two previous studies from our center had looked at acute medical deaths (death within 24 hours) in the emergency, Ajuluchukwu et al 9 , and hypertension-related complications of acute mortality, Mbakwem etal 10 heralding the impact of epidemiological transition.…”
Section: Introductionmentioning
confidence: 99%